2022
DOI: 10.31000/almaal.v4i1.6651
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Hasil Investasi Dana Asuransi Jiwa Syariah di Indonesia Periode 2014-2021

Abstract: This paper aims to analysis the management of Islamic Life Insurance funds in Indonesia. From the OJK report, it was found that the investment returns of Sharia Life Insurance funds often experience losses, even though when viewed from the assets and investment value they have the highest interest compared to Sharia General Insurance and Sharia Reinsurance. The data in this study were obtained from OJK and the financial statements of Indonesian Sharia Insurance companies. This research uses quantitative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
1
0
3
Order By: Relevance
“…These findings align with the conclusions drawn from a study conducted by Warto and Khumaini (2022) titled; "Analysis of Investment Results of Islamic Life Funds in Indonesia for the Period 2014-2021," which indicated that the total investment during that period amounted to only IDR2.485 trillion or 1%. The study recommended that Islamic Life Insurance explore alternative financing sectors beyond the capital market.…”
Section: Source: Iknb Shariah Statistics 2019-2022supporting
confidence: 87%
“…These findings align with the conclusions drawn from a study conducted by Warto and Khumaini (2022) titled; "Analysis of Investment Results of Islamic Life Funds in Indonesia for the Period 2014-2021," which indicated that the total investment during that period amounted to only IDR2.485 trillion or 1%. The study recommended that Islamic Life Insurance explore alternative financing sectors beyond the capital market.…”
Section: Source: Iknb Shariah Statistics 2019-2022supporting
confidence: 87%
“…Tantangan lainnya adalah kompleksitas proses klaim asuransi dan kurangnya pemahaman nasabah tentang manfaat asuransi jiwa (Warto & Khumaini, 2022). Beberapa nasabah mungkin mengalami kesulitan dalam memahami prosedur klaim asuransi, seperti dokumen yang diperlukan dan proses yang harus diikuti.…”
Section: B Manfaat Dan Tantangan Dalam Penggunaan Asuransi Jiwa Dalam...unclassified
“…Kapabilitas dan kapasitas Indonesia dalam menggarap pasar halal, mulai dari sektor makanan, fashion muslim, hingga keuangan syariah, semakin mempertegas bahwa Indonesia bisa menjadi pemain inti dalam ekonomi syariah global. Kebijakan pengembangan ekonomi dan keuangan syariah merupakan upaya Bank Indonesia untuk mendukung kebijakan ekonomi dan keuangan syariah nasional yang bertujuan menjadikan Indonesia sebagai Epicentrum Ekonomi dan Keuangan Syariah Dunia (Warto, 2024).…”
Section: Al-iqtishad: Jurnal Ekonomiunclassified